Metastatic cervical lymphadenopathy masquerading as extrapulmonary tuberculosis (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Cervical lymphadenopathy can be due to various pathologies especially in the young. A high index of suspicion is required in the management of cervical lymphadenopathy to prevent misdiagnosis and wrong treatment.Case report: Here present the diagnostic challenge in the case of a young lady with nasopharyngeal carcinoma who initially presented solely with cervical lymphadenopathy. Previous fine needle aspiration cytology had suggested tuberculosis (TB) and she was commenced on anti-TB drugs. However failure of improvement and worsening symptoms led to another review in ENT clinic. A subsequent nasopharyngeal biopsy confirmed nasopharyngeal carcinoma. She subsequently improved after commencement of appropriate treatment.Conclusion: In regions with a high prevalence rate of tuberculosis, care must be taken to exclude malignancy in patients with cervical lymphadenopathy even when cytology suggests a granulomatous infection. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12030 Bangladesh J Otorhinolaryngol 2012; 18(2): 234-237